Critical Evaluation of the Interaction of Reactive Oxygen and Nitrogen Species with Blood to Inform the Clinical Translation of Nonthermal Plasma Therapy. (3rd December 2020) - Lin, Abraham; Biscop, Eline; Breen, Colum; Butler, Stephen J.; Smits, Evelien; Bogaerts, Annemie
Abstract : Non-thermal plasma (NTP), an ionized gas generated at ambient pressure and temperature, has been an emerging technology for medical applications. Through controlled delivery of reactive oxygen and nitrogen species (ROS/RNS), NTP can elicit hormetic cellular responses, thus stimulating broad therapeutic effects. To enable clinical translation of the promising preclinical research into NTP therapy, a deeper understanding of NTP interactions with clinical substrates is profoundly needed. Since NTP-generated ROS/RNS will inevitably interact with blood in several clinical contexts, understanding their stability in this system is crucial. In this study, two medically relevant NTP delivery modalities were used to assess the stability of NTP-generated ROS/RNS in three aqueous solutions with increasing organic complexities: phosphate-buffered saline (PBS), blood plasma (BP), and processed whole blood. NTP-generated RNS collectively (NO2 −, ONOO − ), H2 O2, and ONOO − exclusively were analyzed over time. We demonstrated that NTP-generated RNS and H2 O2 were stable in PBS but scavenged by different components of the blood. While RNS remained stable in BP after initial scavenging effects, it was completely reduced in processed whole blood. On the other hand, H2 O2 was completely scavenged in both liquids over time. Our previously developed luminescent probe europium(III) was used for precision measurement of ONOO − concentration. NTP-generated ONOO − was detected in all three liquids for up to at least 30 seconds, thus highlighting its therapeutic potential. Based on our results, we discussed the necessary considerations to choose the most optimal NTP modality for delivery of ROS/RNS to and via blood in the clinical context.